Some Biochemical Parameters of Black and White Myrtle communis L. Fruits Subjected to Different Preservation Methods - Bakar, Büşra; Çakmak, Meltem; Özer, Dursun; Karatas, Fikret; Saydam, Sinan (Centenary University, 2021)
In this work, black and white Myrtus communis L. (myrtle) fruits some biochemical parameters were investigated such as vitamins, carotenes, functional peptides, oxidative stress markers (OSM), total phenolic (TP) and flavonoid (TF) substances, antioxidant capacity (AC) and amino acids contents. The black myrtle fruits had generally higher amounts of vitamins, TP, AC and amino acid (AA) contents than the white myrtle fruits. The biochemical contents of myrtle fruits dried in the sun light and microwave (MW) were found to be lower than the frozen fruits (P<0.05). A significant increase was observed in the amount of oxidised glutathione (GSSG) and malondialdehyde (MDA) in myrtle fruits as a result of drying (P<0.05). Amounts of total AA in the black and white myrtle fruits were found to be 31.37 and 21.89 mg g-1 DW, respectively. From the results obtained, it can be said that black myrtle fruit is a better nutrition source than white myrtle fruits and freezing is the most appropriate preservation method. © 2021, Centenary University. All rights reserved.
Farklı Koruma Yöntemlerinin Uygulandığı Siyah ve Beyaz Mersin Meyvelerindeki Bazı Biyokimyasal Parametreler
Keywords: Amino acids; Antioxidant capacity; Myrtle; Phenolic substance; Preservation; Vitamins